PEMBUATAN KEPUTUSAN DALAM KEADAAN RESIKO OLEH KEPALA SEKOLAH - Iskandar Zulkarnain (Manajer Pendididikan, 2016)
This study aims at describing the decision making of risk problem made by the head master. This study is descriptive – qualitative research which uses questionnaire, interview anddocumentation as the technique of collecting the data. To analyze the data, this study makes use of qualitative analysis, percentage and scoring technique. Based on the data analysis, this study concludes that (a) the head master identifies the problems; formulates the goals of the decision making; arranges the solution possibilities, gives solution criterions of each solution possibilities and takes one of them as the final decision, (b) the head master tends to apply the brain storming and synetics techniques and (c) the head master tends to use conceptual style in the decision making process.Keywords: decision making, head master, risk problem